A Causal Assessment of Nigeria’s Crude Oil Revenue, Health Expenditure, and Economic Growth - Awoyemi, Olanike Bosede; Nwibe, Divine Amarachi (International Journal of Energy Economics and Policy, 2022)
Economic growth and health expenditure in Nigeria have become major priorities, and there is no doubt that health expenditure in Nigeria has risen over the years. According to studies, revenue and expenditure are important factors that contribute to a country's economic growth. Using pairwise granger causality, the study investigated the relationship between oil revenue, health expenditure, and economic growth. The variables of interest were oil revenue, health expenditures, real gross domestic product, consumer price index, and money supply. The annual time series data from 1980 to 2020 were obtained from the Central Bank of Nigeria (CBN) statistical bulletin, annual reports, and the World Bank Database. According to the findings, there is a bidirectional relationship between total health expenditure and real GDP. However, there is a unidirectional relationship between oil revenue and GDP. Furthermore, there is a unidirectional relationship between oil revenue and health expenditure. The study concluded that oil revenue and health expenditure granger cause Nigerian economic growth. Therefore, the government should make better use of oil revenue, close loopholes, and increase health spending. To increase productivity and economic growth, the government should increase public spending on health.